An atomically controlled insulator-to-metal transition in iridate/manganite heterostructures - Enyang Men; Deyang Li; Haiyang Zhang; Jingxin Chen; Zhihan Qiao; Long Wei; Zhaosheng Wang; Chuanying Xi; Dongsheng Song; Yuhan Li; Hyoungjeen Jeen; Kai Chen; et al. (Nature Communications)
Abstract All-insulator heterostructures with an emerging metallicity are at the forefront of material science, which typically contain at least one band insulator while it is not necessary to be. Here we show emergent phenomena in a series of all-correlated-insulator heterostructures that composed of insulating CaIrO3 and insulating La0.67Sr0.33MnO3. We observed an intriguing insulator-to-metal transition, that depends delicately on the thickness of the iridate component. The simultaneous enhancements of magnetization, electric conductivity, and magnetoresistance effect indicate a percolation-type nature of the insulator-to-metal transition, with the percolation threshold can be reached at an exceptionally low volume fraction of the iridate. Such a drastic transition is induced by an interfacial charge transfer, which interestingly alters the electronic and crystalline structures of the bulk region rather than the limited ultrathin interface. We further showcased the central role of effective correlation in modulating the insulator-to-metal transition, by demonstrating that the critical thickness of iridate for triggering the metallic state can be systematically reduced down to a single unit-cell layer.